The Level of Participation Among Non-English Major Students in English Classroom Activities - Helena Tada; Chairil Anwar Korompot; Geminastiti Sakkir (PT. Global Research Collaboration, 2025)
This study investigates the level of classroom participation among non-English major students enrolled in English language courses. Employing a quantitative descriptive approach, data were collected through a structured questionnaire distributed to 20 randomly selected first-semester students from the Faculty of Sports and Health Sciences at Universitas Negeri Makassar. The results indicate that 80% of the participants demonstrated active (65%) or very active (15%) involvement in classroom activities, while 20% remained neutral. No students were categorized as passive. The mean participation score of 50 falls within the